Bio-Climatology for the Built Environment - Shukuya, Masanori (Milton : Chapman and Hall/CRC, 2019)
Indoor climate is determined by rational lighting, heating, cooling and ventilating systems. For occupants' well-being it should be consistent with how regional outdoor climate works in the flow of radiation via four paths of heat transfer: radiation; convection; conduction; and evaporation. This book starts with the relationship between the human body and its immediate environmental space followed by a brief introduction of passive and active systems for indoor climate conditioning. The nature of light and heat is discussed with a focus on building envelope systems such as walls and windows, and then examined from the viewpoint of thermodynamics and human-biology. Some examples are given to enable a better understanding of luminous and thermal characteristics of our most immediate environment particularly for those professionally involved in environmental planning, designing, and engineering to know about bio-climatic design principle.
Cover; Title Page; Copyright Page; Dedication; Table of Contents; Preface; 1: Built Environment and Human Beings; 2: Passive and Active Systems for Conditioning the Built Environment; 3: Basics of Human Biology; 4: Solar and Lunar Effects on Built Environment; 5: Visible Light and Luminous Environment; 6: Heat and Thermal Environment; 7: Thermodynamics; 8: Air and Moisture; 9: Mathematical Modelling; 10: Human-Body Exergetic Behaviour; 11: Flow and Circulation of Matter; 12: Global Environmental System Enfolding Built-Environmental Systems; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Buildings -- Environmental engineering; TECHNOLOGY / Construction / General; TECHNOLOGY / Construction / Heating, Ventilation & Air Conditioning; TECHNOLOGY / Industrial Health & Safety